Benzobisthiadiazole and Its Derivative-Based Semiconducting Polymer Nanoparticles for Second Near-Infrared Photoacoustic Imaging - Huang, Xuelong; Lan, Ning; Zhang, Yanfeng; Zeng, Wei; He, Haifeng; Liu, Xiuhong (Frontiers in Chemistry, 2022)
Photoacoustic (PA) imaging has received more and more attention on disease diagnosis and fundamental scientific research. It is still challenging to amplify their imaging ability and reduce the toxicity of inorganic materials and exogenous contrast agents. Semiconducting polymer nanoparticles (SPNs), as a new type of contrast agent, have the advantages of low toxicity, flexible structure adjustment, good photostability, and excellent photothermal conversion efficiency. SPNs containing benzo(1,2-c;4,5-c′)bis(1,2,5)thiadiazole (BBT) units, as the most classic second near-infrared window (NIR-II, 1,000–1700 nm) PA contrast agents, can achieve light absorption in the NIR-II region, thereby effectively reducing light loss in biological tissues and improving imaging resolution. This mini review summarizes the recent advances in the design strategy of BBT and its derivative-based semiconducting polymer nanoparticles for second near-infrared photoacoustic imaging. The evolution process of BBT blocks provides a unique perspective for the design of high-performance NIR-II PA contrast agents.